2006
DOI: 10.1124/jpet.106.112417
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salvinorin A, a κ-Opioid Hallucinogen, on a Neuroendocrine Biomarker Assay in Nonhuman Primates with High κ-Receptor Homology to Humans

Abstract: This study focused on the in vivo effects of the -opioid hallucinogen salvinorin A, derived from the plant Salvia divinorum. The effects of salvinorin A (0.0032-0.056 mg/kg i.v.) were studied in a neuroendocrine biomarker assay of the anterior pituitary hormone prolactin in gonadally intact, adult male and female rhesus monkeys (n ϭ 4 each). Salvinorin A produced dose-and time-dependent neuroendocrine effects, similar to the synthetic high-efficacy -agonist U69,593but of shorter duration than the latter. Salvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…Therefore, the present CSF detection data are consistent with brain -receptor occupancy by salvinorin A, at times when its robust behavioral and neuroendocrine effects are observed (Butelman et al, 2007). It has been pointed out that CSF concentrations of a particular ligand are not necessarily identical to brain extracellular concentrations under all conditions; therefore, this extrapolation should be interpreted with caution (Shen et al, 2004).…”
Section: Downloaded Fromsupporting
confidence: 68%
See 3 more Smart Citations
“…Therefore, the present CSF detection data are consistent with brain -receptor occupancy by salvinorin A, at times when its robust behavioral and neuroendocrine effects are observed (Butelman et al, 2007). It has been pointed out that CSF concentrations of a particular ligand are not necessarily identical to brain extracellular concentrations under all conditions; therefore, this extrapolation should be interpreted with caution (Shen et al, 2004).…”
Section: Downloaded Fromsupporting
confidence: 68%
“…This study determined the effect of salvinorin A (0.032 mg/kg) after 30-min pretreatment with nalmefene (two doses, 0.01 or 0.1 mg/kg s.c., or vehicle). It is known that the smaller nalmefene dose (0.01 mg/kg) is sufficient to cause robust antagonism of -receptor-but not -receptor-mediated effects in this species (France and Gerak, 1994;Butelman et al, 2007). In contrast, nalmefene (0.1 mg/kg) is sufficient to cause antagonism of -receptor-mediated effects in this species.…”
Section: Studies With Sedation and Posture Observational Rating Scalesmentioning
confidence: 91%
See 2 more Smart Citations
“…injection (John et al, 2006). Intravenous administration of Sal A increased prolactin levels in rhesus monkeys, but the duration was only 30 min, shorter than that of U69,593 (90 min) at the same dose (Butelman et al, 2007). A pharmacokinetic study in nonhuman primates showed that the elimination t 1/2 of Sal A in the serum was less than 1 h (Schmidt et al, 2005a).…”
mentioning
confidence: 99%